Peer Support, School Well-Being, Student Engagement Siswa SMP X Denpasar di Masa Pandemi Covid-19 - Mirratul Afifah; Ismira Dewi (Empathy : Jurnal Fakultas Psikologi, 2022)
Peer Support, School Well-Being, Student Engagement at Student SMP X Denpasar during Pandemic Covid-19The purpose of the present study was to examine the relationship between peer support and school well-being with student engagement during covid-19 pandemic. This research method uses a quantitative approach with measuring instruments on the peer support scale, school well-being scale, and student engagement scale. The research subjects were 99 students of JHS students. The data were analysis technique in this study used multiple regression analysis and partial correlation with SPP 24.0 for windows. The result of analysis obtained R of  0.746 with significance level of 0.000 (p > 0.05) meaning that there is a very significant relationship between peer support and school well-being with student engagement. The results of the analysis can be concluded that there is a very significant relationship between peer support, school well-being, and student engagement in junior high school students during covid-19 pandemic with an effective contribution of 55.7%.